Exploring protective mechanisms with triazine ring and hydroxyethyl groups: Experimental and theoretical insights (Kuwait Journal of Science)
The current study investigates the protective mechanisms of a novel triazine-based compound, 2,2′,2''-((1,3,5-triazine-2,4,6-triyl)tris (azanediyl))triethanol (TATTE) (for carbon steel protection in 0.5 M sulfuric acid) were investigated. Potentiodynamic polarization and electrochemical impedance spectroscopy analyses unveiled that TATTE serves as a protective agent with a dual inhibitory mechanism, showcasing exceptional efficiency exceeding 96%. Scanning electron microscopy (SEM) observations demonstrated the formation of a protective layer by TATTE on the surface of carbon steel. Density functional theory (DFT) calculations offered valuable insights into the favorable adsorption of both the neutral and protonated forms of TATTE through interactions between their functional groups and the steel surface. Molecular dynamics simulations further substantiated this, revealing that the neutral molecule exhibits physical adsorption, while the protonated form engages in stronger chemical adsorption, as evidenced by binding energies and radial distribution functions. The superior protective mechanism performance observed in our experiments can be attributed to the synergistic adsorption of TATTE, facilitated by the presence of the triazine ring and multiple hydroxyl groups. © 2024 The Author(s)